2018
DOI: 10.1021/acsami.8b01436
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous Role of Growth-Induced Defects on the Semiconductor-to-Metal Characteristics in Epitaxial VO2/TiO2 Thin Films

Abstract: Controlling the semiconductor-to-metal transition temperature in epitaxial VO thin films remains an unresolved question both at the fundamental as well as the application level. Within the scope of this work, the effects of growth temperature on the structure, chemical composition, interface coherency and electrical characteristics of rutile VO epitaxial thin films grown on TiO substrates are investigated. It is hereby deduced that the transition temperature is lower than the bulk value of 340 K. However, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Usually the variation of the transition temperature has been associated with the stress and microstructure of the samples [28]. In this work, it is likely that the increased defect density may also lead to an increase of T t along the lines in [29]. Another factor is the grain size.…”
Section: Resultsmentioning
confidence: 99%
“…Usually the variation of the transition temperature has been associated with the stress and microstructure of the samples [28]. In this work, it is likely that the increased defect density may also lead to an increase of T t along the lines in [29]. Another factor is the grain size.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the VO 2 transition is accompanied by structural changes, such as V–V dimerization along the c- axis. The dimerization of the V–V chains contributes to the formation of an insulating band gap . It has been reported that Ti atoms gradually diffuse from the TiO 2 layer to the VO 2 layers, leading to the formation of a V x Ti 1– x O 2 solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…The wide range of ordered point defects caused by V n O 2 n –1 (Magnéli phases) or V n O 2 n +1 (Wadsley phases) phases also made it different to synthesize VO 2 with good stoichiometry. , Many methods have been attempted to prepare monoclinic VO 2 material. For example, molecular beam epitaxy, pulsed laser deposition, and magnetron sputtering , are usually used to prepare monoclinic VO 2 epitaxial films, whereas chemical vapor deposition, physical vapor deposition, , hydrothermal method, ion beam lithography technology, and atomic layer deposition technology are used for synthesizing different monoclinic VO 2 nanostructures including nanowires/beams or nanoparticles. It is suggested that the MIT of VO 2 induced phase separations or other emergent phenomena are closely associated with the grain size and boundaries.…”
Section: Introductionmentioning
confidence: 99%